Bacterial Communities in Neonatal Feces are Similar to Mothers’ Placentae - Xu-Dong Dong; Xiao-Ran Li; Jian-Jun Luan; Xiao-Feng Liu; Juan Peng; Yi-Yong Luo; Chen-Jian Liu (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: The gut microbiota plays an important role in human health. It is essential to understand how the composition of the gut microbiota in neonates is established.